Investigation of Mizoroki‐Heck coupling polymerization as a catalyst‐transfer condensation polymerization for synthesis of poly(p‐phenylenevinylene). Issue 4 (2nd December 2014) - Nojima, Masataka; Saito, Ryosuke; Ohta, Yoshihiro; Yokozawa, Tsutomu
ABSTRACT Mizoroki‐Heck coupling polymerization of 1, 4‐bis[(2‐ethylhexyl)oxy]‐2‐iodo‐5‐vinylbenzene (1) and its bromo counterpart 2 with a Pd initiator for the synthesis of poly(phenylenevinylene) (PPV) was investigated to see whether the polymerization proceeds in a chain‐growth polymerization manner. The polymerization of 1 with tBu3PPd(Tolyl)Br (10) proceeded even at room temperature when 5.5 equiv of Cy2NMe (Cy = cyclohexyl) was used as a base, but the molecular weight distribution of PPV was broad. The polymerization of 2 hardly proceeded at room temperature under the same conditions. In the polymerization of 1, PPV with H at one end and I at the other was formed until the middle stage, and the polymer end groups were converted into tolyl and H in the final stage. The number‐average molecular weight (Mn) did not increase until about 90% monomer conversion and then sharply increased after that, indicating conventional step‐growth polymerization. The occurrence of step‐growth polymerization, not catalyst‐transfer chain‐growth polymerization, may be interpreted in terms of low coordination ability of H‐Pd(II)‐X(tBu3P) (X = Br or I), formed in the catalytic cycle of the Mizoroki‐Heck coupling reaction, to π‐electrons of the PPV backbone; reductive elimination of H‐X from this Pd species with base would take place after diffusion into the reaction mixture. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 543–551